Physical Activity Learning Model for Students in Elementary School - Wahyuningtyas Puspitorini; James Tangkudung (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Inactive behavior is closely related to today's technological advances. The school curriculum has reduced students' physical activity because they have more time to participate in academic activities. In children and adolescents, this physical fitness is often forgotten, even though it is very useful to support physical work capacity which is expected to improve their performance. This study aims to create a physical activity program to improve physical fitness in elementary school students. The research method used is ADDIE. Participants in this study were elementary school students total 75 children (49 boys and 26 girls). The instruments used in collecting data were questionnaires and physical fitness tests. The findings of this study indicate that the physical activity program according to expert review is as follows: 1) facilities and infrastructure, 2) adjust the number of sets, duration of implementation, and repetition of each model item, and 3) group the types of activities. 5) arrange each daily physical activity learning program. Meanwhile, from the test results, it is known that this physical activity learning program is feasible and can be carried out by students. While the effectiveness data shows that the physical activity program developed can improve students' physical fitness with a minimum duration of 30 minutes for 3 days a week. The physical activity program developed has proven successful in increasing students' active behavior outside of physical education learning and shows that the movements that are arranged are feasible and effective in improving physical fitness in elementary school students.